Two‐Dimensional Noble‐Metal Chalcogenides and Phosphochalcogenides. Issue 24 (1st April 2020) - Kempt, Roman; Kuc, Agnieszka; Heine, Thomas
Abstract: Noble‐metal chalcogenides, dichalcogenides, and phosphochalcogenides are an emerging class of two‐dimensional materials. Quantum confinement (number of layers) and defect engineering enables their properties to be tuned over a broad range, including metal‐to‐semiconductor transitions, magnetic ordering, and topological surface states. They possess various polytypes, often of similar formation energy, which can be accessed by selective synthesis approaches. They excel in mechanical, optical, and chemical sensing applications, and feature long‐term air and moisture stability. In this Minireview, we summarize the recent progress in the field of noble‐metal chalcogenides and phosphochalcogenides and highlight the structural complexity and its impact on applications. Abstract : The noble art : Noble‐metal dichalcogenides and phosphochalcogenides are a novel class of two‐dimensional materials. This Minireview summarizes the progress in their synthesis, characterization, and application, highlighting their unique structural features and relationships.